Cohort study to evaluate efficacy, safety and acceptability of a two-rod contraceptive implant during third, fourth and fifth year of product use in China - Y Che; D Taylor; D Luo; LY Maldonado; M Wang; S Wevill; H Vahdat; X Han; V Halpern; L Dorflinger; MJ Steiner (Elsevier, 2019)
Objective: Sino-implant (II) is a contraceptive implant approved for 4 years of use in China. We evaluated the contraceptive efficacy during the third, fourth and fifth year, and assessed additional pharmacokinetics (PK), safety, and acceptability endpoints. Study design: We enrolled a cohort of 255 current Sino-Implant (II) users entering their third year and a second cohort of 243 users entering their fourth year. We followed these two cohorts for 12 and 24 months, respectively. To characterize PK endpoints (i.e. levonorgestrel (LNG), sex hormone binding globulin and free LNG index) over 5 years, we collected blood samples in a subset of 50 participants we followed during the third, fourth and fifth year. We also enrolled small cohorts (n = 20) of Sino-implant (II) users entering their sixth month and second year and followed them each for up to 6 months. Our primary efficacy measures were the pregnancy Pearl Indices during Year 3 and 4. Secondary objectives included assessments of PK, safety, acceptability and efficacy in the fifth year. Results: We recorded four pregnancies, with a higher pregnancy rate during Year 3 [1.34 (95% CI: 0.28-3.93)] than Year 4 [0.44 (95% CI: 0.01-2.47)] or Year 5 [0.00 (95% CI: 0.00-2.02)]. The overall pregnancy rate for the third, fourth and fifth years of product use was 0.63 per 100 WY; 95% CI: (0.17-1.62). Mean LNG concentrations remained well above 200 pg/mL (Year 3 = 280.9; Year 4 = 233.6; Year 5 = 270.6). Most participants (93.7%) described their bleeding pattern as acceptable. Conclusion: Sino-implant (II) is a highly effective contraceptive method in this population of Chinese women over 5 years. Implications: Sino-implant (II) is a highly effective contraceptive method with an estimated Pearl Index of less than 1% over the third, fourth and fifth years of use in a population of Chinese women of reproductive age. Keywords: Sino-implant, Levoplant, Long-acting reversible contraceptive, Contraceptive effectiveness, safety